2023
DOI: 10.1039/d3cc00456b
|View full text |Cite
|
Sign up to set email alerts
|

Exsolution on perovskite oxides: morphology and anchorage of nanoparticles

Abstract: In this work, we summarize the current state of research regarding the morphology of exsolved nanoparticles on perovskite oxides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 107 publications
0
18
0
Order By: Relevance
“…Reference crystal structures were taken from the Inorganic Crystal Structure Database provided by the FIZ Karlsruhe. The deposition numbers of the following structures are given in the references: LaFeO 3 (1), LaCoO 3 (2), LaFe 0.5 Co 0.5 O 3 (3), LaNiO 3 (4), LaFe 0.5 Ni 0.5 O 3 (5, 6), LaCo 0.5 Ni 0.5 O 3 (7), La 0.8 Sr 0.2 CoO 3 (8), La 0.8 Ca 0.2 CoO 3 (9), Fe 2 O 3 (10), Fe 3 O 4 (11), Co 3 O 4 (12), NiO (13). The structures of intermediate phases and final products of the perovskites' decompositions are La 3 Co 3 O 8 (14), La 2 Co 2 O 5 (15), CoO (16), Co (17), La 4 Ni 3 O 9.97 (18), LaNiO 2.5 (19), La 4 Ni 3 O 10 (20), La 3 Ni 2 O 7 (21), Ni (22), La 2 O 3 -cubic (23), La 2 O 3 -trigonal (24), SrO (25), CaO (26), and Fe 3 N (27).…”
Section: X-ray Powder Diffractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reference crystal structures were taken from the Inorganic Crystal Structure Database provided by the FIZ Karlsruhe. The deposition numbers of the following structures are given in the references: LaFeO 3 (1), LaCoO 3 (2), LaFe 0.5 Co 0.5 O 3 (3), LaNiO 3 (4), LaFe 0.5 Ni 0.5 O 3 (5, 6), LaCo 0.5 Ni 0.5 O 3 (7), La 0.8 Sr 0.2 CoO 3 (8), La 0.8 Ca 0.2 CoO 3 (9), Fe 2 O 3 (10), Fe 3 O 4 (11), Co 3 O 4 (12), NiO (13). The structures of intermediate phases and final products of the perovskites' decompositions are La 3 Co 3 O 8 (14), La 2 Co 2 O 5 (15), CoO (16), Co (17), La 4 Ni 3 O 9.97 (18), LaNiO 2.5 (19), La 4 Ni 3 O 10 (20), La 3 Ni 2 O 7 (21), Ni (22), La 2 O 3 -cubic (23), La 2 O 3 -trigonal (24), SrO (25), CaO (26), and Fe 3 N (27).…”
Section: X-ray Powder Diffractionmentioning
confidence: 99%
“…Catalysts prepared by exsolution have an exceptionally strong particle‐support interaction, hindering these processes [10] . This is due to their anchorage, meaning the nanoparticles are seated in an indentation on the support material [11] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,20−27 In particular, the exsolution of Ni NPs has been extensively investigated for high-temperature catalysis and electrocatalysis. 28,29 These studies have shown that exsolved Ni NPs exhibit specific interactions with their parent oxide compared to NPs externally dispersed onto perovskites using conventional impregnation methods due to their embedded structure within the perovskite support. For instance, exsolved Ni NPs were found to be more resistant to agglomeration 5 and coking during high-temperature methane steam reforming, which are two catalyst deactivation causes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an A-site deficient perovskite (A 1– x BO 3 ) can boost the irreversible exsolution of NPs, which become socketed in the oxide support. This exsolution process has been studied using noble metals such as Ru, Rh, Pd, and Pt, as well as transition metals including Fe, Co, Ni, and Cu, in many different conditions. , In particular, the exsolution of Ni NPs has been extensively investigated for high-temperature catalysis and electrocatalysis. , These studies have shown that exsolved Ni NPs exhibit specific interactions with their parent oxide compared to NPs externally dispersed onto perovskites using conventional impregnation methods due to their embedded structure within the perovskite support. For instance, exsolved Ni NPs were found to be more resistant to agglomeration and coking during high-temperature methane steam reforming, which are two catalyst deactivation causes.…”
Section: Introductionmentioning
confidence: 99%